New challenges and opportunities for low-field MRI - Anoardo, Esteban (2023)
In this manuscript we deal with recent advances in low-field Magnetic Resonance Imaging (MRI). The development of low-cost MRI solutions allowing portability and trustable diagnosis is a hot topic worldwide by these days. We analyze basic technical issues of recent examples of fixed-field instruments operating at low-field. Then we discuss pros and cons of the pre-polarized approach, from both physical and technical perspectives. Permanent magnet and electromagnet technology are confronted. Finally, magnetic field-cycling is introduced as an alternative MRI technique, where field-dependent experiments can be exploded for the development of new contrast mechanisms that are not feasible for fixed-field MRI instruments. As field cycled machines usually deals with switched currents in electromagnets, magnetic field instability and inhomogeneity are the main limiting factors affecting image quality. We finalize this manuscript discussing how it turns possible to overcome these limitations, thus opening new possibilities for the development of cost effective MRI technology.